Innovative Digital Curriculum and RUMSDIAM E-Module for Community Health Volunteers: Evidence from a Quasi-Experimental Study on Diabetes Education Outcomes - Meildy Esthevanus Pascoal; Ana Barnetje Montol; Kevin Giovani Pascoal (Yayasan Keluarga Guru Mandiri, 2026)
Community health volunteers are vital for diabetes management within primary healthcare, but traditional training models often limit their educational progress. This study evaluates the efficacy of an ADDIE-structured digital curriculum and e-module, RUMSDIAM (Rumah Sehat Diabetes Mellitus or Diabetes Mellitus Healthy Home), to boost diabetes literacy among volunteers. A quasi-experimental pre-post test control group design involved 50 participants; the intervention group engaged with the RUMSDIAM e-module, while the control group utilized conventional materials. Results: RUMSDIAM received superior validation from experts and exhibited usability. Post-intervention scores surged, significantly outperforming the control group. The experimental group achieved a high N-Gain and an extremely large effect size. The RUMSDIAM digital curriculum effectively empowers grassroots health workers. This study contributes to science by establishing a systematically validated digital model that bridges the gap in structured education for community-level volunteers, confirming that systematic digitalization offers a transformative pathway for health technology integration in community settings.